Epidemiology, pathophysiology and diagnosis of uveitic glaucoma and ocular hypertension secondary to uveitis - Łazicka-Gałecka, Monika; Guszkowska, Maria; Gałecki, Tomasz; Dziedziak, Jacek; Kamińska, Anna; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
Uveitic glaucoma (UG) encompasses a broad spectrum of disorders leading to an increase in intraocular pressure (IOP) and glaucomatous damage to the optic nerve in patients with concomitant uveitis. The treatment of glaucoma in patients with uveitis requires a meticulous diagnostic and therapeutic approach, often involving a multidisciplinary team, to achieve adequate control of the inflammatory response and IOP. As researchers have been able to pinpoint the risk factors for elevated IOP in patients with uveitis, it has become possible to identify groups of patients who require special attention in clinical practice. The variety of mechanisms underlying the development of UG is associated primarily with the type of uveitis. Most patients with active inflammation experience a decrease in IOP due to reduced production of the aqueous humor and increased uveoscleral outflow. In some cases, however, IOP is elevated, for example during active trabeculitis, chiefly in patients with uveitis of herpetic origin. Chronic inflammation may cause scarring and remodeling within the Schlemm’s canal, collecting channels, and trabecular meshwork, leading to an increased resistance to the outflow of the aqueous humor. IOP elevation due to the filtration angle closure mechanism in patients with active uveitis occurs most commonly through the formation of posterior synechiae, anterior synechiae or neovascular membranes in the filtration angle itself. In addition, the possibility of iatrogenic IOP elevation in patients with uveitis during treatment with glucocorticoids (mainly topical, but also systemic) must be considered. Making a correct diagnosis of uveitis and regular patient follow-up for glaucomatous damage are of crucial importance. Accurate diagnosis allows for prompt implementation of appropriate anti-inflammatory treatment, helping to avoid long-term effects of smoldering inflammation.